Zika virus RNA detection in asymptomatic blood donors during an outbreak in the northeast region of São Paulo State, Brazil, 2016. Issue 12 (16th September 2017) - Slavov, Svetoslav N.; Hespanhol, Marta R.; Rodrigues, Evandra S.; Levi, José E.; Ubiali, Eugênia M.A.; Covas, Dimas T.; Kashima, Simone
Abstract : BACKGROUND: In 2015, there was a large Zika virus (ZIKV) outbreak in Brazil. The proportion of asymptomatic infections is very high, and it is possible for transfusion‐transmitted ZIKV (TT‐ZIKV) infection to occur. The prevalence of asymptomatic ZIKV infection among Brazilian blood donors during this epidemic outbreak is unknown. STUDY DESIGN AND METHODS: Plasma samples obtained between October 2015 and May 2016 from 1393 volunteer blood donors were tested for ZIKV RNA. The viral load was quantified using an in‐house standard curve. Additionally, positive ZIKV RNA samples were tested for anti‐ZIKV immunoglobulin (Ig)M and anti‐ZIKV IgG. RESULTS: Of the 1393 blood samples, ZIKV RNA was detected in 37 (n = 37/1393; 2.7%). The median infection viral load detected was 7714 copies/mL (ranging from 135‐124, 220 copies/mL). The majority of the positive samples (70.3%) exhibited a viral load of approximately 10 3 copies/mL. Six samples that were positive for ZIKV RNA were also positive for anti‐ZIKV IgM and IgG (n = 6/37; 13.5%). CONCLUSION: This is the first study evaluating the prevalence of ZIKV RNA among Brazilian blood donors, which was relatively high and might lead to TT‐ZIKV infection. It is unclear whether the simultaneous presence of anti‐ZIKV IgM and IgG in RNA‐positive donations or the viral load influences transfusion transmission of the infection. This study also adds to the global understanding of ZIKV prevalence in blood donors during outbreaks and the transfusion impact of the infection.